BOʻLAJAK TARIX OʻQITUVCHILARINING KASBIY KOMPETENTLIGINI RIVOJLANTIRISHNING TASHKILIY-PEDAGOGIK SHART-SHAROITLARI - Bobonorov, X.T. (SCIENCE and SOCIETY, 2025)
The article reveals the mechanisms for enhancing the professional skills of future history teachers. The criteria for assessing the level of professional competence of students have been clarified, and the main conditions that ensure their development in the field of pedagogical activity have been identified. Furthermore, the experience of developing students’ professional qualities has been systematized and summarized as an integral component of teacher professional development.